2013
DOI: 10.1212/01.wnl.0000436942.55281.47
|View full text |Cite
|
Sign up to set email alerts
|

Nonamnestic mild cognitive impairment progresses to dementia with Lewy bodies

Abstract: Objective: To determine the rate of progression of mild cognitive impairment (MCI) to dementia with Lewy bodies (DLB). Methods:We followed 337 patients with MCI in the Mayo Alzheimer's Disease Research Center (range 2-12 years). Competing risks survival models were used to examine the rates of progression to clinically probable DLB and Alzheimer disease (AD). A subset of patients underwent neuropathologic examination.Results: In this clinical cohort, 116 remained as MCI, while 49 progressed to probable DLB, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
207
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(224 citation statements)
references
References 42 publications
15
207
0
2
Order By: Relevance
“…He strongly supported the belief that RBD, when diagnosed by Polysomnogram, might be the strongest risk factor for DLB when compared with other signs [6,7]. In a study of patients with non-amnestic mild cognitive impairment (MCI) who progressed to DLB a year later, about half of the patients had RBD which was more common than two other features of DLB, Visual Hallucinations and Parkinsonism [8].…”
mentioning
confidence: 88%
“…He strongly supported the belief that RBD, when diagnosed by Polysomnogram, might be the strongest risk factor for DLB when compared with other signs [6,7]. In a study of patients with non-amnestic mild cognitive impairment (MCI) who progressed to DLB a year later, about half of the patients had RBD which was more common than two other features of DLB, Visual Hallucinations and Parkinsonism [8].…”
mentioning
confidence: 88%
“…3,4 We have previously demonstrated that the competing risk of progression to probable DLB vs AD is higher in patients with nonamnestic MCI compared to amnestic MCI. 5 Hippocampal volumes on antemortem MRI are preserved in patients with DLB who have little or no additional AD pathology at autopsy. [6][7][8] Hippocampal volumes are lower in patients with DLB with increasing Braak neurofibrillary tangle stage regardless of the severity of Lewy body disease pathology.…”
mentioning
confidence: 97%
“…Impairment in nonamnestic cognitive domains, particularly in the attention and visual-spatial processing domains, increases the risk for probable DLB in MCI. 4,5,23 While nonamnestic MCI is characterized by relative preservation of hippocampal volumes, hippocampal atrophy may be present in some patients with nonamnestic MCI. 22 Furthermore, hippocampal atrophy is common in patients with multiple-domain amnestic MCI, and these patients are at risk for both probable DLB and AD dementia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, this could help in predicting the conversion of MCI as has been reported by Ferman et al that naMCIs were more likely to develop dementia with Lewy body (DLB) while patients with aMCI are more likely to convert to AD (Ferman, et al, 2013).…”
Section: Alzheimer's Diseasementioning
confidence: 92%